Secession and Security Explaining State Strategy against Separatists - Butt, Ahsan I. (Cornell Studies in Security Affairs, 2017)
Since World War II, separatist conflicts have been the most common and deadly types of war in international politics. Such wars result from a simple incongruity: ethno-nationalist groups desire a homeland, but on territory that is controlled by states unwilling to give it up. This book examines states' strategies, particularly their use of violence, when confronted by separatist movements. Using more than 110 interviews, American and British diplomatic archives, and newspaper archives, this book's emphasis on external security can account for separatist violence, or its lack thereof, in a variety of historical contexts including Pakistan's treatment of Bengali secessionists; India's treatment of separatism in Assam, Punjab, and Jammu and Kashmir; interactions between the Ottoman Empire and Armenia; and Israel's attitudes toward Palestine.